Histopathological pattern of primary ovarian neoplasms in south‑western Nigeria (2016)
Background: Ovarian tumours are common forms of neoplasms in women. This study aims to determine the histopathological pattern of primary ovarian neoplasms in south-western Nigeria. Method: A retrospective study was undertaken to review the histopathology reports of all primary ovarian neoplasm specimens submitted to the Department of Pathology, University College Hospital, Ibadan from January 1991 to June 2013. Patients’ biodata were extracted from request forms and surgical day books. Results: There were 821 cases of primary ovarian neoplasms. Surface epithelial neoplasms accounted for 359 (43.7%) of cases and were found in patients aged 10–89 years. Germ cell tumours numbered 313 (38.0%) in patients aged 0–70 years, while sex cord stromal tumours numbered 146 (17.8%) in patients aged 0–99 years. Among benign ovarian neoplasms, Mature Cystic Teratoma was the most common (54.7%) with the 20–29 year age range having the highest frequency. Among primary malignant ovarian neoplasms, serous cystadenocarcinoma was the most common (33.2%) and most frequent in the 50–59 year age group. Conclusion: Surface epithelial tumours were the most common ovarian neoplasms followed by germ cell tumours. This histopathological pattern is observed in most parts of Nigeria, some African and Asian countries, and in the Western world.